Murder on Wall Street - Thompson, Victoria (Victoria E.) (New York, NY : Berkley Prime Crime, 2022)
Reformed gangster Jack Robinson is working hard to bolster his image in Gilded Age New York City society as he prepares to become a new father. But when Hayden Norcross, the man who nearly ruined his wife, is shot in cold blood, Jack knows the police will soon come knocking on his door. Frank Malloy has to agree--things dont look good for Jack. But surely a man as unlikeable as Hayden had more than a few enemies. And its soon clear that plenty of the upper echelon as well as the denizens of the most squalid areas of the city seem to have hated him. Sarah and Frank have their work cut out for them. As the daughter of the elite Decker family, Sarah has access to the social circles Hayden frequented, and the more she learns about his horrific treatment of women, the more disturbed she becomes. And as Frank investigates, he finds that Hayden had a host of unsavory habits that may have hastened his demise. But who finally killed him? Sarah and Frank must put the pieces together quickly before time runs out and Jacks hard-won new life and family are ripped apart.
Keywords: Brandt, Sarah (Fictitious character) -- Fiction; Malloy, Frank (Fictitious character) -- Fiction; Midwives -- Fiction; Private investigators -- Fiction; Murder -- Investigation; Fiction; Bankers -- Fiction; Rich people -- Fiction; Socialites -- Fiction; Scandals -- Fiction; New York (N.Y.) -- Social life and customs -- 19th century; Fiction; New York (N.Y.) -- History -- 1865-1898; Fiction; Detective and mystery fiction